2011
DOI: 10.1007/s00787-011-0235-8
|View full text |Cite
|
Sign up to set email alerts
|

The decisions regarding ADHD management (DRAMa) study: uncertainties and complexities in assessment, diagnosis and treatment, from the clinician’s point of view

Abstract: Background: Clinical decision making is influenced by a range of factors and constitutes an inherently complex task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 26 publications
6
63
0
1
Order By: Relevance
“…These include: (i) partial or nonresponse; 3 (ii) possible adverse effects; 4 (iii) uncertainty about long term costs and benefits; 5 (iv) poor adherence; 6 and (v) negative medication-related attitudes from patients, parents or clinicians. 7 Psychological treatments such as behavioral parent training are also widely used. However, a recent meta-analysis 8 found no effects on ADHD symptoms when only ratings by assessors blind to treatment allocation were considered.…”
Section: Introductionmentioning
confidence: 99%
“…These include: (i) partial or nonresponse; 3 (ii) possible adverse effects; 4 (iii) uncertainty about long term costs and benefits; 5 (iv) poor adherence; 6 and (v) negative medication-related attitudes from patients, parents or clinicians. 7 Psychological treatments such as behavioral parent training are also widely used. However, a recent meta-analysis 8 found no effects on ADHD symptoms when only ratings by assessors blind to treatment allocation were considered.…”
Section: Introductionmentioning
confidence: 99%
“…The IPAQ was developed on the basis of the key themes derived from qualitative analysis of semi-structured interview data carried out in the Decisions Regarding ADHD Management (DRAMa) study [27]. The DRAMa study focused on the uncertainties and complexities in assessment, diagnosis and treatment of ADHD from the clinician's point of view (for more detailed information and results, please refer to Kovshoff et al [27].…”
Section: Methods Measurementioning
confidence: 99%
“…The DRAMa study focused on the uncertainties and complexities in assessment, diagnosis and treatment of ADHD from the clinician's point of view (for more detailed information and results, please refer to Kovshoff et al [27]. On the basis of inductive thematic analysis of 50 interviews with consultant psychiatrists and paediatricians, ten themes were identified that related to medication-related decision making.…”
Section: Methods Measurementioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that different mechanisms leading to a respective mental disorder are present in routine clinical care than in research settings, thus rendering deviations from treatment protocols mandatory [23]. These differences raise concerns that treatments tested in RCTs may not be applicable to patients treated in routine clinical care [32], because the adherence to a predefined sequence of sessions with predetermined therapy contents in RCTs may constrain the therapist's ability to adapt each therapy session to the individual treatment needs of a patient.…”
Section: Conceptual Aspectsmentioning
confidence: 99%